2000
DOI: 10.1093/bja/85.4.628
|View full text |Cite
|
Sign up to set email alerts
|

Use of nitric oxide for decompensated right ventricular failure and circulatory shock after cardiac arrest

Abstract: We describe a case of peri-operative cardiac arrest, severe right ventricular failure and pulmonary hypertension in a 60-yr-old woman with interstitial pulmonary fibrosis. Inhaled nitric oxide therapy rapidly improved arterial oxygenation and haemodynamic variables, allowing recovery and weaning from mechanical ventilation. Subsequently, the patient was discharged from the cardiac intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Institution of iNO treatment has been described previously for treatment of pulmonary embolus, pulmonary hypertension and AFE [8, 14]. In this case the ability to perform and evaluate a transthoracic ultrasound rapidly both confirmed the diagnosis and the response to iNO treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Institution of iNO treatment has been described previously for treatment of pulmonary embolus, pulmonary hypertension and AFE [8, 14]. In this case the ability to perform and evaluate a transthoracic ultrasound rapidly both confirmed the diagnosis and the response to iNO treatment.…”
Section: Discussionmentioning
confidence: 54%
“…This minimizes systemic vasodilatation, although it necessitates continuous delivery into the ventilator circuit [206]. NO selectively reduces PVR and improves CO in PAH [212], secondary PH [205,213,214], acute PE [215,216], ischemic RV dysfunction [217,218], and postsurgical PH [202,219-234]. NO also improves oxygenation [235], RVEF, and reduces vasopressor requirements in PH after cardiac surgery [236], especially in patients with higher baseline PVR [237], with no augmented effect seen at doses above 10 ppm in these patients [238].…”
Section: Resultsmentioning
confidence: 99%
“…The crucial role of endothelium-derived NO in the maintenance of a normal cardiac function and the inhibition of adverse ventricular remodeling is well established [17,18]. In line with this, it has been shown that administration of NO improves the left ventricle diastolic function in HF patients [19] and that chronic inhibition of the endogenous NO production is associated with severe myocardial fibrosis in animal models [20].…”
Section: Discussionmentioning
confidence: 95%